Perlindungan dan Pengembangan Bisnis UMKM Melalui Skema Pemberian Izin PIRT di Desa Jarin Kabupaten Pamekasan - Alfina Damayanti; Moh. Soleh (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
UMKM in Jarin Village, Pamekasan Regency face various challenges in developing their businesses. One of the challenges faced is the suboptimal protection and development of their businesses, many of which do not yet have a NIB or even a PIRT. The investigative approach employed is a type of empirical legal inquiry utilizing a field study methodology (Field Research). Data gathering for this investigation involved various techniques such as interviews, observations, and literature reviews. The study's location is situated in Jarin Village, within the Pademawu District of Pamekasan Regency. The data analysis technique applied in this research is descriptive-qualitative. Findings from the study during the MBKM KKNT indicated that the UMKM present in Jarin Village, Pademawu District, Pamekasan Regency are limited in number, only a handful. Among these is an UMKM focused on the Krupuk Opak and Jagung Goreng venture, which maintains a marketing scope that remains at the regional tier. Furthermore, business operators have yet to secure a PIRT certificate, despite the fact that legally, those in the food or snack industry are mandated to acquire PIRT in accordance with the Food and Drug Supervisory Agency Regulation Number 4 of 2024 related to Guidelines for Issuing Certificates of Commitment Fulfillment for Home-Processed Food Production, therefore KKNT participants provide assistance to the Pamekasan Regency Health Office for the issuance of PIRT. It is proven that after obtaining a P-IRT permit, the product marketing network has increased and sales have increased and the legality of the business is strong.